Experience-Dependent Color Constancy in Guppies (Poecilia reticulata) - I. E. Intskirveli; M. O. Roinishvili; A. R. Kezeli (Neural Plasticity)
We investigated the ability to recognize the color of surfaces in fish (Poecilia reticulata), bred from birth in conditions of artificial light with constant spectral content. The capacity for color constancy significantly deteriorated when compared that to the control group. Further alteration of lighting conditions and transfer into natural daylight conditions restored the suppressed function to its normal level. We suggest that the color constancy function belongs in the visual system-response functions, the full development of which requires the accumulation of individual visual experience.